PENGARUH DEBT TO EQUITY RATIO, INSIDER OWNERSHIP, SIZE, DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN (Studi pada Industri Manufaktur yang terdaftar di Bursa Efek Indonesia Periode Tahun 2005-2007) - Mulyono, Budi (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2010)
This study is performed to examine the effect of Debt to Equity Ratio (DER), Insider Ownership, Size and Investment Opportunity Set (IOS) toward Dividend Policy in manufacturing company which is listed in BEJ and share the dividend to shareholder. The objective this study is to scale and analyze the effect of the company financial ratios performance Debt to Equity Ratio (DER), Insider Ownership, Size and Investment Opportunity Set (IOS) toward Dividend Payout Ratio (DPR) in manufacturing company which is listed in BEJ over period 2005-2007.Sampling technique used here is purposive sampling on criterion (1) the company that trade their stocks in Bursa Efek Jakarta; (2) the company that represent their financial report per December 2005 – 2007; and (3) the company that continually share their dividend per December 2005 – 2007. The data is obtained based on Indonesia Capital Market Directory (ICMD 2008) publication. It is gained sample amount of 17 companies from 151 companies those are listed in BEJ. The analysis technique used here is multiple regressions with the least square difference and hypothesis test using t-statistic to examine partial regression coefficient and F-statistic to examine the mean of mutual effect with level of significance 0,05 or 5%. In addition, classical assumption is also performed including normality test, multicolinearity test, heteroscedasticity test and autocorrelation test.From the analysis result, it indicates that DER and Ln IOS variable partially significant toward DPR of the company on 2005-2007 period on the level of significance less than 5%, while it indicates that Ln Insider Ownership and Size variable partially not significant toward DPR. While simultaneously DER, Ln Insider, Size, Ln IOS proof significantly influent DPR in BEJ in level less than 5%. Predictable of four variables toward DPR is 43,3% as indicated by adjusted R square that is 43,3% while the rest 56,7% is affected by other factors which are not included into the study model.